Juego y su influencia en el desarrollo de la motricidad gruesa en los niños de Educación Inicial I - Barragán Yépez, Nathalia Andreina (2025)
The following research project analyzes how the application of different games impacts the progress of gross motor skills in children in Early Childhood Education at the Aurora Estrada y Ayala de Ramírez Pérez Educational Institution, located in Babahoyo, Los Ríos Province. Although it is a crucial educational tool to promote motor, social and emotional skills, there is a lack of systematic playful strategies that promote motor growth in this institution. The main purpose of the research is to develop educational tactics that encourage the progress of gross motor skills through leisure activities. The specific objectives include evaluating the effect of current recreational activities, detecting aspects to improve in the execution of said activities and suggesting an intervention plan to enhance motor growth in children. The approach used includes direct observation, interviews with teachers and the study of the existing educational infrastructure. It is anticipated that the findings of the study will underline the relevance of a structured organization of games to promote motor growth. As a possible conclusion, the study proposes that the implementation of more structured leisure strategies will significantly contribute to the comprehensive growth of children, promoting both their physical and emotional health. As a possible recommendation, implement a systematic program of educational games focused on the development of gross motor skills at the Aurora Estrada y Ayala Educational Institution in Ramírez Pérez. This program should be planned and executed in a structured manner, incorporating recreational activities that promote motor, social and emotional skills in children.